Feasibility of an eight‐week outpatient‐based pulmonary rehabilitation program for advanced lung cancer patients undergoing cytotoxic chemotherapy in Korea. Issue 8 (22nd June 2018) - Park, Young Sik; Lee, Jinwoo; Keum, Bhumsuk; Oh, Byung‐Mo
Abstract : The scientific evidence supporting pulmonary rehabilitation (PR) for lung cancer patients undergoing cytotoxic chemotherapy is accumulating; however, the feasibility of outpatient‐based PR in these patients has not yet been evaluated in Korea. We conducted an eight‐week outpatient‐based PR feasibility study in a tertiary referral hospital setting. Patients with advanced lung cancer (non‐small cell lung cancer IIIB–IV and small‐cell lung cancer extensive disease) scheduled to undergo first‐line cytotoxic chemotherapy underwent PR consisting of 60‐minute sessions twice a week under the guidance and supervision of a physical therapist, for a total of eight weeks. Feasibility was assessed based on completion of the PR program. In total, 12 patients (median age 68 years) were enrolled; 11 (91.7%) were male with a history of smoking. Among these 12 patients, 9 (75%) completed the eight‐week outpatient‐based PR program. Three patients could not complete the PR program: two were unwilling and one died from complications of lung cancer. This study showed a 75% completion rate of an eight‐week outpatient‐based PR program for advanced lung cancer patients undergoing cytotoxic chemotherapy, which supports its feasibility.